Empowering mothers in fulfilling preconception nutrition: Stunting prevention strategy - Pasaribu, Rina Doriana; Surbakti, Elisabeth; Saragih, Hanna Sriyanti (Institute of Computer Science (IOCS), 2024)
Preventing stunting from an early age is one of the Ministry of Health's strategies for tackling stunting in Indonesia. This community service aims to empower partners as agents of Change who collaborate with the community service team to empower mothers with teenage children through nutritional education to ensure preconception nutrition. This empowerment method in community service is the implementation of participatory action research. Empowerment targets are cognitively and economically empowered to fulfill preconception nutrition. Community service will occur in Pantai Labu Village, Pantai Labu District, Deliserdang Regency. A pre and post-assessment was carried out on the empowerment targets to evaluate the impact of this empowerment. Data collection methods were carried out using questionnaires, observations, and interviews. Data analysis using the Paired T-test if the data is usually distributed, and if the data is not normally distributed, the Wilcoxon test is used. The results showed an increase in knowledge and attitudes. Knowledge and attitudes of Preconception Nutrition Change Agent Training Participants (p-value < 0.05). Change Agents were committed to health promotion in Pantai Labu Village. Moreover, there was an increase in mothers' knowledge and attitudes about preconception nutrition (p-value < 0.05).